Family violence and suicidal ideation in adolescents at the San Juan Bautista de Huaral Hospital - Minetto Acuña, Ailee Berna (2013)
This study determined the relationship between family violence and suicidal ideation in adolescents, establishing correlations between abuse forms and suicidal ideation. It is a descriptive, correlational study and a non-experimental, crossed design was used. It was a non-probability sampling. The sample consisted of 100 adolescents of both sexes, whose ages ranged from 12 to 17 years old. They were treated at the psychology service of San Juan Bautista hospital in Huaral during August-October 2012. The instruments used were the family violence and child abuse screening chart (modified ad hoc) and suicidal ideation Beck scale. The results revealed that in most cases, the adolescents had a mean level of family violence and a high level of suicidal ideation. Furthermore, a significant correlation between family violence and suicidal ideation (r = 0,656) was found, and also significant correlations between psychological abuse (r = 0,476), physical abuse (r = 0,431), and negligence (r = 0,413). A relation between family violence and suicidal ideation by gender (women: r = 0,662) and age group (15-17a: r = 0,707) was found.